PERFORMANCE MANAGEMENT (PM) THROUGH PRIME-HRM: A CASE STUDY OF THE PROVINCE OF BUKIDNON - Pryncz Leinor Paraiso; Christine Tenorio (Indonesian Journal of Social Sciences, Policy and Politics, 2024)
Performance management is a critical component of effective human resource management, particularly in the public sector, where accountability and service excellence are paramount. The Philippine government has taken a major step to improve performance management procedures in the public sector with the Program to Institutionalize Meritocracy and Excellence in Human Resource Management (PRIME-HRM). Using a qualitative case study methodology, the study focuses on important provincial stakeholders, such as the heads of Agencies, the Provincial Human Resource Management Office (PHRMO), and Rank and File Employees. According to the results, the Province of Bukidnon has made great progress in adhering to the PRIME-HRM performance management regulations and guidelines established by the Civil Service Commission (CSC). Key elements of the program, including goal-setting, performance evaluation, feedback, and performance improvement planning, have been implemented successfully, improving employee performance and work satisfaction. The report also emphasizes how PRIME-HRM performance management has improved decision-making on career advancement, incentives, and promotions. The province has demonstrated its commitment to SHRM priorities by integrating performance management approaches with organizational goals. The importance of these findings for the Province of Bukidnon and other public sector organizations looking to improve their performance management procedures is emphasized in the study's conclusion. The results offer insightful information about the effective execution of PRIME-HRM and a road map for coordinating performance management with strategic objectives and cultivating an excellence culture in the public sector.